Influence of Additives and Temperature on the Interaction of Acid Red 151 Dye with Cetyltrimethylammonium Bromide: A Conductometric Study. Issue 5 (13th May 2020) - Nur, Asaduzzaman; Mahbub, Shamim; Rahman, Mohammad Majibur; Khan, Farah; Rub, Malik Abdul; Hoque, Md. Anamul; Khan, Mohammed Abdullah; Azum, Naved; Asiri, Abdullah M.
Abstract: The interaction of an anionic textile dye, acid red 151 (AR), with a cationic surfactant, cetyltrimethylammonium bromide (CTAB), in aqueous electrolyte medium (e.g., KCl, NaCl) and in H2 O + ethanol medium was observed using the conductometric method. Two critical micelle concentrations ( CMC ) were found for the AR + CTAB system in water and H2 O + ethanol medium, but only one CMC was detected for AR + CTAB in salt+H2 O media and for pure CTAB in all solutions. The change in CMC behavior of CTAB in the presence of AR indicates the occurrence of strong interaction between AR and CTAB. The extent of solubility increases with an increase of temperature, which disfavors micellization. The CMC values in NaCl solution are comparatively lower than those found in KCl solution, which signifies that the micelle formation is more favorable in attendance of NaCl. In aqueous ethanol solution, two CMC values were also observed for AR + CTAB that are higher than those obtained in water. The free energy of micellization ( ∆ G m 0 ) was negative, which illustrates a thermodynamically spontaneous micellization process. The values of enthalpy ( ∆ H m o ) and entropy ( ∆ S m o ) of micellization show that the process was entirely entropically driven at a lower temperature; but, enthalpic events are favored at elevated temperature in electrolyte medium, whereas both enthalpy and entropy are reduced in attendance of ethanol. In aqueous medium, the thermodynamic parameters signify the presence of electrostatic interaction between AR and CTAB at higher temperatures, while the hydrophobic interaction is the main driving force at a lower temperature. A linear expression of ∆ H m o as a function of ∆ S m o demonstrates enthalpy‐entropy compensation over the experimental conditions employed in this study.